Opini Audit dan Reaksi Pasar: Apakah Penerapan GRC Memperkuat Keterkaitannya? - Stiawan, I Kadek Jonh (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to analyze the effect of audit opinion on market reaction with the moderating effect of Governance, Risk, and Compliance (GRC) implementation. This study was conducted on banking sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, with a population of 47 banking sector companies. Sampling used purposive sampling, obtaining a sample of 8 companies with a 5-year observation period, resulting in a total of 40 observation data. Data collection was carried out using documentation techniques from IDX data available on the website. Analysis using Moderated Regression Analysis (MRA) with the help of the STATA program. The results of the study found that audit opinion was unable to influence market reaction and GRC implementation also did not moderate the relationship between the two. This finding indicates that non-financial factors such as audit opinion and GRC have not become the primary focus of investors, who rely more on financial information and the company's fundamental performance.